Cultmap_ cartografias artísticas urbanas - Andres, Carolina Reichert (2013)
Born surfaces analyzed the city of Santa Maria, RS - valid on daily commutes by public roads along the thought of worship places of urban art - the research called Cultmap_artistic urban cartographies establishes links between urban art - graffiti, sticker and stencil - geography rigged. Covers the ownership of artistic urban interventions in the city through a visual catalogue georeferenced places of demonstrations. This becomes exploitable by methods geotechnology when the acquisition method of digital geographical information, included in the use of GPS (Global Positioning System), GIS (Geographic Information System) and Remote Sensing. Based also disclosing the data captured in the WWW as poetic research, the proposed web art which is also titled Cultmap (www.cultmap.com.br).